Development of e-Module based on Simulation PhET Fluid Material Dynamic in Senior High School - Fitriyawany, Fitriyawany; Julita, Fena; Mustika, Cut Rizki (Universitas Syiah Kuala, 2023)
The facts obtained in the field are that technology-based learning media has not been used, there is a lack of teaching materials in the learning process, and inadequate laboratory facilities. The aim of this research is to design an e-module based on PhET simulation in fluid dynamics material for Senior High School and determine its feasibility. The method used in this development research (RD) is which refers to the development model developed by Alessi and Trollip which consists of three stages including (1) Planning, (2) Design and (3) Development. The research subjects consisted of 3 media experts and 3 material experts. The instrument used is a validation sheet. Data collection was carried out through questionnaires and analyzed descriptively qualitatively. The product resulting from this research is an e-module based on PhET Simulation Fluid Dynamic Material in senior high school. The results of material expert validation were obtained with a total percentage of 88.25%, while media expert validation obtained a total percentage of 97.62%. The resulting categories are classified into feasible criteria. The results of this research can be used as a solution to be applied in the learning process.